MALAYSIA STROKE CONFERENCE 2022 4: Oral Presentation - 2022, Malaysia Stroke Conference (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
1. BALANCE TRAINING TO IMPROVE HAND FUNCTION IN STROKE: A SCOPING REVIEW 2. CHALLENGES IN DELIVERING TELE-REHABILITATION FOR RURAL COMMUNITIES IN MALAYSIA 3. INTERNATIONAL CLASSIFICATION OF FUNCTIONING, DISABILITY AND HEALTH AS PREDICTORS FOR PATIENT OUTCOME 4. PREDICTORS OF POST STROKE UNFAVORABLE FUNCTIONAL OUTCOMES AMONG PATIENTS WITH HYPERGLYCEMIA DURING ACUTE ISCHEMIC STROKE 5. THERAPIST’S ROLE IN THERAPEUTIC ALLIANCE FOR THE PATIENTS’ ENGAGEMENT IN STROKE REHABILITATION 6. COVID-19 VACCINATION, INFECTION, AND RISK OF STROKE IN MALAYSIA 7. EFFECTIVENESS OF VOCATIONAL REHABILITATION AUGMENTED WITH COGNITIVE REMEDIATION THERAPY FOR STROKE SURVIVORS WITH COGNITIVE IMPAIRMENTS IN IMPROVING WORK READINESS: A RANDOMISED CONTROLLED TRIAL 8. DEVELOPING A MALAY LANGUAGE EXECUTIVE FUNCTION ASSESSMENT: A SURVEY WITH SPEECH-LANGUAGE PATHOLOGISTS IN MALAYSIA (Non-clinical study)